2011
DOI: 10.1378/chest.10-1504
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Among Health-Related Quality of Life, Pulmonary Health, and Newborn Screening for Cystic Fibrosis

Abstract: Medical advances have signifi cantly improved the longevity of patients with cystic fi brosis (CF). The median survival age is approximately 37 years, and many patients live well into middle age. 1 Newborn screening (NBS) is an innovation that provides early intervention for affected infants. Although neo natal diagnosis offers nutritional advantages, over time, patients experience complications that require increasingly complex treatments 2-4 for which they and their families typically shoulder most of the bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 24 publications
(31 reference statements)
1
24
0
4
Order By: Relevance
“…Koscik and colleagues (29) reported a link between NBS diagnosis and improved cognitive outcomes, but failed to demonstrate any benefit for HRQoL (7). On the other hand, delayed diagnosis in the face of clinical symptoms is in itself a major source of anxiety for parents, leading to lack of trust in the medical profession and to "doctor shopping" (30). Most parents appear to be supportive of NBS, in the belief that early detection and intervention will improve the health of their children and reduce the stress of a delayed diagnosis (30,31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Koscik and colleagues (29) reported a link between NBS diagnosis and improved cognitive outcomes, but failed to demonstrate any benefit for HRQoL (7). On the other hand, delayed diagnosis in the face of clinical symptoms is in itself a major source of anxiety for parents, leading to lack of trust in the medical profession and to "doctor shopping" (30). Most parents appear to be supportive of NBS, in the belief that early detection and intervention will improve the health of their children and reduce the stress of a delayed diagnosis (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, delayed diagnosis in the face of clinical symptoms is in itself a major source of anxiety for parents, leading to lack of trust in the medical profession and to "doctor shopping" (30). Most parents appear to be supportive of NBS, in the belief that early detection and intervention will improve the health of their children and reduce the stress of a delayed diagnosis (30,31). This positive parental attitude might affect patients' beliefs and the likelihood of developing psychological distress, as suggested by Szyndler et al (22) who attributed the low levels of psychopathology found in adolescents to the large screening uptake in Australia.…”
Section: Discussionmentioning
confidence: 99%
“…Broad information have been distributed uncovering falling apart personal satisfaction and psychosocial working as an aftereffect of a wide range of complexities [33][34][35][36][37][38]. In a meta-examination, Body Mass Index (BMI) classifications were connected with higher all-reason and reason particular mortality; peril proportions (HR) 0.94 for overweight and 1.18 for heftiness all evaluations joined [9].…”
Section: Treatment Of Morbiditymentioning
confidence: 99%
“…33). Despite what might be expected, it was watched that there was an expanded number of postagent inconveniences in the populace that had an Operation performed (Chances Proportion 6.0571).…”
Section: Introductionmentioning
confidence: 99%
“…Newborn screening is also estimated to provide a small mortality benefit (41,42). However, a follow-up study of patients in the randomized trial of newborn screening, now between 8 and 18 years of age, showed no benefit from newborn screening for pulmonary disease or health-related quality of life (43). The evolution toward screening that offered less dramatic benefit was described by one expert as moving from ''public health emergency'' to ''public health service'' (44).…”
Section: Expansion Of Newborn Screeningmentioning
confidence: 99%